A phase I/II trial of WT1-specific TCR gene therapy for patients with acute myeloid leukemia and active disease post-allogeneic hematopoietic cell transplantation: skewing towards NK-like phenotype impairs T cell function and persistence - Mazziotta, Francesco; Martin, Lauren E.; Egan, Daniel N.; Bar, Merav; Kinsella, Sinéad; Paulson, Kelly G.; Voillet, Valentin; Lahman, Miranda C.; Hunter, Daniel; Schmitt, Thomas M.; Duerkopp, Natalie; Yeung, Cecilia C. S.; et al. (Nature communications, 2025)
Relapsed and/or refractory acute myeloid leukemia (AML) post-allogeneic hematopoietic cell transplantation (HCT) is usually fatal. We previously reported that post-HCT immunotherapy with Epstein-Barr virus (EBV)-specific donor CD8 + T cells engineered to express a Wilms Tumor Antigen 1-specific T-cell receptor (T TCR-C4 ) appeared to prevent relapse in high-risk patients. In this phase I/II clinical trial (NCT01640301), we evaluated safety (primary endpoint), persistence and efficacy (secondary endpoints) of EBV- or Cytomegalovirus (CMV)-specific T TCR-C4 in fifteen patients with active AML post-HCT. Infusions were well tolerated, with no dose-limiting toxicities or serious adverse events related to the product. However, T TCR-C4 cells did not clearly improve outcomes despite EBV-specific T TCR-C4 cells showing enhanced potential for prolonged persistence compared to CMV-specific T TCR-C4 . Investigating the fate of persisting T TCR-C4 , we identified a shift towards natural killer-like (NKL) terminal differentiation, distinct from solid tumor-associated canonical exhaustion programs. In one patient, treatment with azacitidine appeared to mitigate this NKL skewing, promoting T TCR-C4 persistence. These findings suggest that AML drives a distinct form of T-cell dysfunction, highlight the need for targeted approaches that preserve T-cell fitness, ultimately improving the efficacy of cellular therapies for AML. Relapsed and/or refractory acute myeloid leukemia (AML) postallogeneic hematopoietic cell transplantation has limited treatment options. Here the authors report the clinical results and immune correlates of a phase I/II trial of adoptively transferred virus-specific donor CD8 + T cells engineered to express a WT1-specific T cell receptor in patients with acute myeloid leukemia and active disease post-allogeneic hematopoietic cell transplantation.